2016
DOI: 10.1080/17454832.2015.1125382
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Art Therapy Large Group, an educational tool in the training of art therapists, on post-qualification professional practice

Abstract: This article reports the findings of a Likert scale survey that was sent to past graduates of the MA Art Psychotherapy, Goldsmiths, University of London asking them about the relevance of their experience in the Art Therapy Large Group (ATLG) to their subsequent employment as art therapists or work in another capacity. The ATLG comprises all the students and staff in a psychodynamically based experiential group that meets six times during the year. Survey questions were drawn from previously devised theory and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…As a result of the development of the hypothesis of a close relationship between soft skills and the competitiveness of students in the labour market, the author presents a schematic model, which demonstrates not only the importance of each of the selected groups of soft skills in general competitiveness, but also close relationship of these concepts, taking into account the changing factor of modern requirements of employers and the labour market in general [14,22,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the development of the hypothesis of a close relationship between soft skills and the competitiveness of students in the labour market, the author presents a schematic model, which demonstrates not only the importance of each of the selected groups of soft skills in general competitiveness, but also close relationship of these concepts, taking into account the changing factor of modern requirements of employers and the labour market in general [14,22,27].…”
Section: Discussionmentioning
confidence: 99%
“…If there is no positive outcome, it may be the result of poor implementation of the educational process. Thus, family breeding, the social environment of the student, and higher education together are important in the formation and development of soft skills [3,27].…”
mentioning
confidence: 99%
“…Our previous theory (Skaife and Jones, 2009; Skaife, Jones and Pentaris, 2016) spoke of specific learning outcomes for the ATLG. Our research has shown that we cannot know what a learning outcome will be prior to any group or session taking place, it has to be found, or re-found each time.…”
Section: Resultsmentioning
confidence: 99%
“…More recently Skaife et al (2016) gave a likert scale survey to 142 past graduates of the programme over a six-year period. The survey sought to find out if the learning objectives delineated in the 2009 articles had validity.…”
Section: Part Onementioning
confidence: 99%